(untitled) (Journal of Hama University, 2025)
This study aimed to identify the impact of the gross domestic product on the financial structure of Islamic banks in Syria during the period (2010-2020) and to determine the nature of the relationship that exists between them, because of its great importance in the context of maintaining economic stability and growth. To achieve this goal, the method was used. Simple linear regression, depending on the nature of the data and knowing the existence of an impact of the GDP on the financial structure and knowing the nature of this impact. The study reached several results, the most important of which is the presence of a statistically significant effect of the GDP on the financial structure of Islamic banks. It also turned out that 53.4% of the changes occurring in the financial structure are explained by changes in the GDP. A linear equation was formulated that represents the relationship between the two variables.